Chinese nutraceuticals and physical activity; their role in neurodegenerative tauopathies - Abdullahi Alausa; Sunday Ogundepo; Barakat Olaleke; Rofiat Adeyemi; Mercy Olatinwo; Aminat Ismail (BMC, 2021)
Abstract The onset of neurodegenerative disease has not only been a major cause of scientific worry, but of economic burden to the health system. This condition has been further attributed to mis-stability, deletion or mutation of tau protein, causing the onset of Corticobasal degeneration, Pick's diseases, Progressive supranuclear palsy, Argyrophilic grains disease, Alzheimer's diseases etc. as scientifically renowned. This is mainly related to dysregulation of translational machinery, upregulation of proinflammatory cytokines and inhibition of several essential cascades such as ERK signaling cascade, GSK3β, CREB, and PKA/PKB (Akt) signaling cascades that enhances protein processing, normal protein folding, cognitive function, and microtubule associated tau stability. Administration of some nutrients and/or bioactive compounds has a high tendency to impede tau mediated inflammation at neuronal level. Furthermore, prevention and neutralization of protein misfolding through modulation of microtubule tau stability and prevention of protein misfolding is by virtue few of the numerous beneficial effects of physical activity. Of utmost important in this study is the exploration of promising bioactivities of nutraceuticals found in china and the ameliorating potential of physical activity on tauopathies, while highlighting animal and in vitro studies that have been investigated for comprehensive understanding of its potential and an insight into the effects on human highly probable to tau mediated neurodegeneration.